2021
DOI: 10.3390/nu13041120
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Characteristics and Trends in the Consumption of Ultra-Processed Foods in Korea from 2010 to 2018

Abstract: There is growing evidence for a global transition to a more highly processed diet. While the dietary share of ultra-processed foods depends on a country’s economic status, food choice and consumption are also influenced by the socioeconomic situation of individuals. This study investigated whether ultra-processed food consumption differed across socioeconomic subgroups and over time (2010–2018) in Korea. Cross-sectional data from the Korea National Health and Nutrition Examination Survey 2010–2018 were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 68 publications
(152 reference statements)
6
56
1
1
Order By: Relevance
“…Regarding age, studies generally reported large variations amongst the age groups. However, UPF intake generally decreased with increasing age, with the highest levels of UPF intake observed in children and adolescents, and the lowest in older subjects [ 51 , 54 , 87 , 104 , 108 , 110 , 112 , 118 ] ( Table 3 ). Only five studies also stratified results based on body mass index (BMI) of the participants, generally finding a slight, but higher, UPF intake in subjects with the highest BMI (e.g., greater than 30 kg/m 2 ) [ 58 , 87 , 89 , 95 ] ( Table 4 ) [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding age, studies generally reported large variations amongst the age groups. However, UPF intake generally decreased with increasing age, with the highest levels of UPF intake observed in children and adolescents, and the lowest in older subjects [ 51 , 54 , 87 , 104 , 108 , 110 , 112 , 118 ] ( Table 3 ). Only five studies also stratified results based on body mass index (BMI) of the participants, generally finding a slight, but higher, UPF intake in subjects with the highest BMI (e.g., greater than 30 kg/m 2 ) [ 58 , 87 , 89 , 95 ] ( Table 4 ) [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Parental education level can be used to reflect socioeconomic status. Family income is another indicator of socioeconomic status that should be adjusted in the regression model because a previous study demonstrated its association with UPFs consumption [ 20 ]. Unfortunately, however, our study lacks information on family income and family status, and this may be a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…UPFs have become a major part of diets in almost every corner of the world because they are widely available, cheap, and aggressively marketed [ 17 , 18 , 19 ]. At the individual level, consumption behaviors are also influenced by several factors, including socioeconomic determinants (such as sex, age, education level, income) [ 20 ], nutritional knowledge, and individual health status (such as physical and psychological well-being) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have assessed the amount of energy consumed from UPFs in different countries. Accordingly, the consumption of UPFs accounts for approximately 25–60% of total energy intake using individual-level data [ 7 , 8 , 9 , 10 ]. UPF energy consumption was highest in the USA and the United Kingdom, while the lowest levels were found in Italy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%